2022
DOI: 10.3389/fphys.2021.823734
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Ramie Powder at Various Levels on the Production Performance, Serum Biochemical Indices, Antioxidative Capacity, and Intestinal Development of Laying Hens

Abstract: The purpose of this study was to investigate the effects of ramie (0, 3, 6, and 9%) included in diets on production performance, antioxidative capacity, serum biochemical indices, and intestinal development of laying hens. A total of 432 Lohmann commercial laying hens were randomly allotted to one of four dietary treatments and fed for 6 weeks. The results showed that the inclusion of ramie had no negative effects on laying performance, and increased (quadratic, P < 0.05) the laying rate with the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The VH, CD and VH:CD ratio are essential parameters for evaluating absorption and digestion capacity in the small intestine. 41,42 The better the development of VH, the stronger the secretion ability of enzymes, and the depth of the crypt is closely related to the intestinal digestion and decomposition ability. 43 A higher VH:CD ratio indicates the integrity of the small intestine's morphological structure and a better absorption capacity of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The VH, CD and VH:CD ratio are essential parameters for evaluating absorption and digestion capacity in the small intestine. 41,42 The better the development of VH, the stronger the secretion ability of enzymes, and the depth of the crypt is closely related to the intestinal digestion and decomposition ability. 43 A higher VH:CD ratio indicates the integrity of the small intestine's morphological structure and a better absorption capacity of the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Ramie leaves contain 17 amino acids, with a total amino acid content of 18.36% [ 3 ]. In addition, previous studies had shown that ramie leaves contain a variety of bioactive components, which have antioxidant, blood lipid-lowering, and intestinal development effects [ 4 , 5 , 6 ]. Therefore, it is practical to assess the impact of ramie as a new feed ingredient in poultry.…”
Section: Introductionmentioning
confidence: 99%